(untitled) (Ukrainian Journal of Ophthalmology, 2026)
Background. Assessment of the extraocular muscle (EOM) mobility is often not made due to difficulty of existed methods. It often leads to inaccurate estimation of operation scope in strabismus patients. Purpose. To develop simple and rapid method of EOM mobility assessment. Material and methods. To solve the task software was developed to picture volunteers’ eyeballs: for both eyeballs the program calculated pupil center shift relative to pupil center position in the primary gaze for each gaze position in millimeters. 120 volunteers without EOM pathology and refraction anomalies were examined with the described method — 60 children of 4—18years old and 60 adults of 19— 55years old. Results. The results obtained proved to be reliable- the biggest eyeball shifts were noted in the horizontal and oblique gaze positions. Maximal shifts from primary gaze equaled 6.5 mm in adults and 5.5 mm in children. The examination lasted up to 5 min. Conclusion. Simple and quick automated method allowing assessment of EOM status was developed. Reference intervals of binocular eyeball movement volumes of healthy volunteers without EOM pathology were obtained.